Ganglion cysts in the lateral portal region of the knee after arthroscopy: report of two cases - Cem Sever; Melih Malkoc; Turker Acar; Faik Turkmen; Ozgur Korkmaz; Onur Oto (Autopsy and Case Reports, 2015)
A ganglion cyst (GC) is a mucinous or gelatinous-filled benign tumor overlying a joint or tendon sheath, which commonly arises in the dorsal and volar wrist side but may occur anywhere in the body. Although cystic lesions around the knee are common, the occurrence of GCs are rare. Ganglia may arise from intra or extra-articular, soft tissue, intraosseous, or periosteal location. Symptoms may vary according to the size and location. After the more frequent performance of magnetic resonance imaging for the assessment of a knee joint, the number of incidental, asymptomatic lesions have been increasingly diagnosed. The etiology of GC remains unclear; however, trauma and a flaw in the joint tissues may explain its appearance. The authors report two cases of women aged 47 years and 37 years who presented pain and swelling in their left knees following arthroscopic partial medial meniscectomy. The former was surgically treated and had a favorable outcome, while the latter had conservative treatment and a gloomy outcome